Management of personnel : manpower management and organizational behavior - Dunn, J. D.; Stephens, Elvis C. (New York : McGraw Hill Education, 1972)
This text differs significantly from other personnel management books in several important ways. First, it emphasizes the results to be achieved by the performance of the personnel management function. Results are expressed in terms of two concepts - employee productivity and employee satisfaction. These criteria are not new; however, in a competitive democratic society committed to full employment all students of personnel management should have an understanding of these basic concepts.
Part I. The Management of Human Resources -- Part II. The Employment of Manpower -- Part III. Employee Productivity-Motivation and Ability -- Part IV. Employee Productivity-Situational Factors -- Part V. Employee Satisfaction -- Part VI. Environmental Factors and Restraints -- Part VII. Organizational Relations with Employees -- Part VIII. A Look Ahead.
Includes index.
Keywords: PERSONNEL MANAGEMENT